(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
A new series of 5-benzylidene-3-(5-ethyl-[1,3,4]thiadiazol-2-yl)-2-phenyl-thiazolidin-4-ones (3a-3m) were synthesized. The reaction of thioglycolic acid with benzylidene-(5-ethyl-[1,3,4] thiadiazol-2-yl)-amine 1a in the presence of anhydrous ZnCl2 afforded the new heterocyclic compounds 5-benzylidene-3-(5-ethyl-[1,3,4] thiadiazole-yl)-2-phenyl-thiazolidin-4-one, 2a. The latter product on treatment with several selected substituted aromatic aldehydes in the presence of sodium ethoxide underwent the Knoevenagel reaction to yield 5-benzylidene-3-(5-ethyl-[1,3,4] thiadiazol-2-yl)-2-phenyl-thiazolidin-4-ones, 3a-3m. The structures of the compounds were confirmed by IR, 1H-NMR, 13C-NMR and mass spectroscopy and by chemical analysis. All the above compounds were screened for their antimicrobial activity against some selected bacteria and fungi such as E. coli, B. Subtilis, and S. Typhi bacteria and A.niger, A. Flavus and F. oxisporium Fungi. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 155-170, 2018